The XTH Gene Family in Schima superba: Genome-Wide Identification, Expression Profiles, and Functional Interaction Network Analysis - Yang, Zhongyi; Zhang, Rui; Zhou, Zhichun (Frontiers in Plant Science, 2022)
Xyloglucan endotransglucosylase/hydrolase (XTH), belonging to glycoside hydrolase family 16, is one of the key enzymes in plant cell wall remodeling. However, little is known about XTHs in Schima superba. In the present study, 34 SsuXTH genes were divided into three subfamilies with phylogenetic analyses and were unevenly distributed on 18 chromosomes. Their protein motifs and gene structures were highly conserved, and their subcellular localization was predicted to be in the cell wall and cytoplasm. Fragment replication and tandem duplication events occurred simultaneously across the SsXTHs, and most genes were subjected to strong purifying selection during the course of evolution. In addition, SsuXTH genes could respond to multiple hormones and abiotic stresses; notably, the expression might also be regulated by MYBs, MYCs, HD-Zips, GATAs, etc. Additionally, a functional interaction network showed that SsuXTH16 interacted with ERFs, MYB77, and WRKY40. Furthermore, the expression profiles revealed that most tandem repeat genes were involved in cell wall remodeling and fiber elongation in S. superba. The GO annotation proved that the XTH enzyme mainly participated in glycoside metabolism through transferase and hydrolase activities in the cell wall and then regulated cell wall remodeling.